Investigation of tribological issues in microforming: a review - Ali, Mohammad Yeakub; Maleque, Md. Abdul; Banu, A.; N., Atiqah (2011)
This paper presents the extensive review of microtribology especially as encountered in microforming. Microforming is one of the most frequently used mass production processes by replication. Micro injection moulding, micro deep drawing, micro casting, and hot embossing are the examples of microforming. These processes are suitable for near net shape or even net shape production. One of the main problems encountered in microforming is the scaling effect that occurs in the tribological aspects; for example, the friction coefficient increases with decreasing specimen size. Scaling effects occur not only within the process but also throughout the forming chain. So, the microforming process can be simplified if the tribological problem is minimized. In this paper a methodology for the investigation and minimization of microtribological issues through the control of micromachining processes has been proposed. Keywords: Tribology, microtribology, microforming, micromachining.